Cambodia : Can New and Improved Preschools Improve Child Development in Rural Communities? - Berkes, Jan; Bouguen, Adrien; Filmer, Deon; Fukao, Tsuyoshi (World Bank, Washington, DC, 2020)
Early childhood is a critical period for growth and development. Research shows that giving young children enough nurturing and stimulating experiences during these early years not only improves their chances of success in school but can also help them succeed and be more productive later in life. Although access to preschool has increased substantially in recent years, in many low-income communities’ children don’t receive any educational services before they start primary school. In some cases, parents aren’t aware of the value of early education and might not take advantage of opportunities to enroll their children in preschool, even when services are available.